ANALYSIS OF INSTITUTIONAL REFORM OF THE INDONESIAN WAQF BOARD (BWI) AND PROBLEMS OF NATIONAL WAQF GOVERNANCE - Nurul Aulia Dewi; Tetty Handayani Siregar; Yenni Samri Juliati Nasution; Marliyah Marliyah (JURNAL PROFIT, 2025)
This study aims to analyze the institutional challenges and direction of reform within the Indonesian Waqf Board (BWI) in managing national waqf. Although Indonesia has enormous waqf potential, with over 414,000 hectares of waqf land and approximately 420,000 nazhirs (Islamic trustees), the reality is that only about 10% of these assets have been managed productively. This study uses a qualitative approach with library research through analysis of academic literature, policy documents, and official reports from related institutions. The results indicate that the main problems lie in weak coordination between the central and regional BWI, limited human resource capacity, a lack of transparency and accountability, and low literacy and public trust in waqf management institutions. Furthermore, the implementation of waqf regulations has not been optimal due to lengthy bureaucracy and the absence of regulations that adapt to contemporary waqf innovations such as digital waqf and stock waqf. Comparisons with Malaysia and Turkey demonstrate that the success of productive waqf management is largely determined by institutional professionalism, strong regulatory support, and the integration of public policy with technology and the Islamic financial sector. Therefore, BWI institutional reform needs to focus on professionalizing nazhir (managers), digitizing the national waqf management system, and developing fiscal policies that encourage productive waqf innovation. These reforms are expected to strengthen transparent, accountable, and globally competitive national waqf governance to achieve the welfare of the community in accordance with the principles of maqāṣid al-syarī‘ah (the main objectives of Islamic law)